Notch Regulation of Hematopoiesis, Endothelial Precursor Cells, and Blood Vessel Formation: Orchestrating the Vasculature - Vincenza Caolo; Daniel G. M. Molin; Mark J. Post (Stem Cells International)
The development of the vascular system begins with the formation of hemangioblastic cells, hemangioblasts, which organize in blood islands in the yolk sac. The hemangioblasts differentiate into hematopoietic and angioblastic cells. Subsequently, the hematopoietic line will generate blood cells, whereas the angioblastic cells will give rise to vascular endothelial cells (ECs). In response to specific molecular and hemodynamic stimuli, ECs will acquire either arterial or venous identity. Recruitment towards the endothelial tubes and subsequent differentiation of pericyte and/or vascular smooth muscle cells (vSMCs) takes place and the mature vessel is formed. The Notch signaling pathway is required for determining the arterial program of both endothelial and smooth muscle cells; however, it is simultaneously involved in the generation of hematopoietic stem cells (HSCs), which will give rise to hematopoietic cells. Notch signaling also regulates the function of endothelial progenitor cells (EPCs), which are bone-marrow-derived cells able to differentiate into ECs and which could be considered the adult correlate of the angioblast. In addition, Notch signaling has been reported to control sprouting angiogenesis during blood vessels formation in the adult. In this paper we discuss the physiological role of Notch in vascular development, providing an overview on the involvement of Notch in vascular biology from hematopoietic stem cell to adaptive neovascularization in the adult.